Socioeconomic disparities in health outcomes and access to health care cross three lands in Comoros. - ASSANHOU, Assogba Gabin (My University, 2017)
The purpose of this paper is two-fold. First, to give an overview of the size and measure trends in health inequalities in the Comoros islands (Comoros) since 1996. Second, to assess the wide differences in health and health care across rural/urban areas and islands in Comoros, by using available and comparable leading indicators, in order to promote regular monitoring of policy goals. This assessment is aimed at reducing health inequalities and providing adequate or equal access to health care between islands. Data from the Demographic and Health Survey, Multiple Indicators Cluster Surveys from 1996, 2000 and 2012, the World Health Organization, the World Bank, the African Development Bank data sources, were analyzed for a population health-oriented approach characterized by measuring health differences from the population average, taking account of the population size of the social groups on both relative and absolute scales. The results showed that there exist geographic disparities in health in Comoros, mainly in maternal and child health.